Devolution as a Panacea to Deeply Divided Multi-Ethnic (National) States: The Continuing Kenyan Experiment - O Mbori, Harrison (Strathmore Law Journal, 2021)
The multiple designers of Kenya’s 2010 Constitution intended that devolution should address the many years of economic exclusion that many Kenyan communities had suffered. While this paper concedes that the design of the 2010 Constitution to a large extent achieves this role, the same constitution fails at engendering national multi-ethnic unity. This paper uses three broad approaches to assess Kenya’s devolution experiment under Kenya’s 2010 Constitution and ethnic unity: the first is Daniel Posner’s Institutional Politics approach, the second is Donald Horowitz’s Constitutional Ethnic Federalism approach, and the final one is Yash Pal Ghai’s Constitutional Autonomy approach. The author argues that limiting our focus to these three approaches as applied in this paper, there is no constitutional design that can easily achieve the lofty objective of national multi-ethnic unity in Kenya. This is because Kenya has had deeply ethnicised politics and social relations that are tied to ethnic political patrons and elites who are always at the forefront of constitutional design outcomes. This explains why even with the 2010 Constitution’s attempt to weaken the imperial presidency, many Kenyans still perceive ascendancy to the presidency as the zenith of social, economic, and political actualisation. The paper, therefore, concludes that the Posner and Horowitz approaches above have merits and demerits and have also been variously applied under the 2010 Kenyan Constitution. The Ghai approach has neither been contemplated nor applied in the 2010 Kenyan Constitution. It emerges that even if the demerits under the Posner, Horowitz, and Ghai approaches were eradicated, which might be quite difficult or even impossible, and yet the zero-sum competitive politics for the presidency persists, the politicisation of ethnicity and the conflicts that stem from this will persist.